(untitled) (Proceedings of the International Conference on Education, 2021)
In medicine, the awareness of reducing medication errors and risk situations for patients has increased in recent years, due to different driving forces such as patient advocate movements, and quality management strategies of health centers and regulatory bodies. However, this awareness should be reflected in the integration of strategies to prevent errors and risks by training medical students, residents, and specialists in patient safety principles. The inclusion of technologies for tridimensional visualization, such as virtual reality enables the development of innovative training proposals that contribute to a patient safety culture. The objective of this project was to design a virtual reality environment for the training on patient safety culture by triangulating the perspectives of teachers, the hospital, and the school of medicine. The development consisted of the phases of planning, design, and implementation. Planning referred to the development of learning objectives and conceptualization of scenarios. The design consisted of the technical exploration of the different tools, and the iteration on the generation of a working prototype. As a result, a virtual setting was developed for medical students to familiarize themselves and understand the environment and the processes of quality care. The reported experience proposes key elements for new developers to consider, the link to the needs of the organization, and the technical feasibility of the systems that are now available in the market.